Hematological parameters in Oreochromis niloticus cultivated in tropical conditions in experimental farm Santo Domingo of University of Amazonia, Florencia, Caquetá, Colombia. - Galindo Peña, Leidy Vanessa; Pérez Cuervo, Frey David; Murcia Ordoñez, Betselene; Chaves Moreno, Luis Carlos; Martínez Moyano, Edgar; Poche Ceballos, Alba Miriam; Hernández Sánchez, José Heli (Scientia et Technica, 2019)
The hematological parameters were evaluated in the Oreochromis niloticus species, weighing between 120 and 375 g, where chemical standards of water were included (T °, pH and OD), morphometry and haematological diagnosis, carried out at the Santo Domingo Experimental Farm from the University of the Amazonia, Florencia - Caquetá-Colombia. A directed and completely random sampling of 32 individuals was used, the blood was extracted by cardiac puncture and placed in Eppendorf tubes with EDTA. Blood smears were stained with Ema staining color for its laboratory analysis. The InfoStat was applied as a statistical method for the analysis of the variables to be measured. A total of leukocytes of 1.11 celx105 / mm3 was found, predominating neutrophils with 49.3% followed by lymphocytes with 38.8%, monocytes with 5.9%, eosinophils with 4.3%, basophils with 1.7 % and thrombocytes with 63.8% as an independent series. For the red series, an average of erythrocytes of 1.5 celx106 / mm3, hemoglobin of 7.9 g / dL; hematocrit of 23.3%, plasma proteins 3.3 g / dL, mean corpuscular volume 165 (u3), mean corpuscular hemoglobin 55 (uug) and mean corpuscular hemoglobin concentration of 33.3%. In conclusion, it was determined that some individuals presented Leukopenia with Lymphopenia and thrombocytosis. In addition, two individuals presented Normochromic Microcytic Anemia (AMN) and 19 individuals presented Normochromic Normocitic Anemia (ANN). The analysis of Total Plasma Proteins (PPT) determined that the high mortality rate was not due to nutritional deficiency. There was a positive similarity between the VCM and HCM, and negatively with the total number of erythrocytes